An enhanced MOSFET threshold voltage model for the 6–300 K temperature range. (February 2017) - Dao, Nguyen Cong; Kass, Abdallah El; Azghadi, Mostafa Rahimi; Jin, Craig T.; Scott, Jonathan; Leong, Philip H.W.
Abstract: An enhanced threshold voltage model for MOSFETs operating over a wide range of temperatures (6–300K) is presented. The model takes into account the carrier freeze-out effect and the external field-assisted ionization to address the temperature dependence of MOS transistors. For simplicity, an empirical function is incorporated to predict short channel effects over the temperature range. The results from the proposed model demonstrate good agreement with NMOS and PMOS transistors measured from fabricated chips. Highlights: A threshold voltage model for MOSFETs operating from 6 K to 300 K is proposed. The freeze-out effect and the field-assisted ionization are included in the model. A simple function predicting short channel effects with temperature is presented.